Clinical Behavior in Sanur, Denpasar-Bali Application of the Homey Concept to Building Structuring and Interior Design - Cahyani, Putu Ayu Indah Gita; Siwalatri, Ni Ketut Ayu; Bagus Suryada, I Gusti Agung (Journal of A Sustainable Global South, 2018)
Giving birth is something that must be experience or the nature of woman. In addition to joy the newest family member, giving birth could bring some negative impact and even take the mother’s life so that raises fear to carry out the labor process. Gentle birth is known as a natural birth that preparing mother's mental to undergo labor, which is focuses on the relaxation, comfortable, safety and privacy in the delivery. Planning a maternity clinic facility with natural living theme that has a home atmosphere is suitable to decrease stress level and feel calm. Sanur strategic area is a potential location to support activities related to relaxation and an activity without any interferences, Sanur is also a great place to attract foreign tourist to the facility. Mother will never be separated from her child, so the purpose of maternity clinic facility is to accom- modate all integrated facilities including health facilities and physical treatments for mother and child from age of 0-5 years (toddlers) aimed at supporting the birthing process itself. Index Terms — clinic, mother, toddler, natural, birth, architecture.